2020
DOI: 10.1111/imcb.12347
|View full text |Cite
|
Sign up to set email alerts
|

Specific antigen‐guiding exosomes inhibit food allergies by inducing regulatory T cells

Abstract: The therapies for food allergy (FA) need to be improved. The generation of inducible regulatory T cells (Tregs) can support immune tolerance in the body. This study aims to suppress experimental FA by inducing Tregs through the employment of modified exosomes (mExosomes). In this study, mExosomes were prepared by incubating dendritic cells with interleukin (IL)‐2 and ovalbumin (OVA, used as a specific antigen) in the culture. Exosomes were purified from culture supernatant and used as the mExosomes. A murine F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The association between Tert expression in intestinal DCs and the FA response was tested. A FA murine model was established with reported procedures [15] (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The association between Tert expression in intestinal DCs and the FA response was tested. A FA murine model was established with reported procedures [15] (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…In a different study, it was shown that MSC-derived exosomes alleviate atopic dermatitis [97]. Interestingly, regulatory DCs stimulated with IL-2 and antigen produce exosomes carrying IL-2 and p-MHCII complexes which promote Tregs and suppress allergic inflammation in a murine model of food allergy [98]. This concept fits into the strategy of expanding T regs via IL-2, which has been a promising and fast-evolving field, including in allergy immunotherapy [99,100].…”
Section: "Tolerosomes" For the Suppression Of Allergic Th2 Responsesmentioning
confidence: 98%
“…A main goal in allergy immunotherapy is the induction of regulatory T cells. Exosomes derived from IL-2 primed tolerogenic DCs were shown to promote regulatory T cells[98]. Additionally, MSC derived exosomes promote regulatory T cells[96].…”
mentioning
confidence: 99%
“…In a different study it was shown that MSC-derived exosomes alleviate atopic dermatitis [83]. Interestingly, regulatory DCs stimulated with IL-2 and antigen produce exosomes carrying IL-2 and p-MHCII complexes which promote Tregs and suppress allergic inflammation in a murine model of food allergy [84]. This concept fits into the strategy of expanding of T regs via IL-2, which has been a promising and fast-evolving field, including in allergy immunotherapy [85], [86].…”
Section: "Tolerosomes" For the Suppression Of Allergic Th2 Responsesmentioning
confidence: 99%